Semiotics of Family Conflict in the Film Ipar Adalah Maut 2024 - Febrina, Maria; Suviai, Vivi; Sinurat, Franciska Lamtiurma Yunita (Riwayat: Educational Journal of History and Humanities, 2025)
This study examines the conflict in the family between a husband and his sister-in-law depicted in the film "Ipar Adalah Maut". This study aims to analyze the signs of communication that appear in the relationship, as reflected through various elements in the film. The method in this study is descriptive qualitative with media text analysis and reinforced by Roland Barthes' semiotic theory. The data collection technique is in-depth analysis that focuses on the main source, namely the film "Ipar Adalah Maut". The analysis process is carried out by identifying communication patterns through two levels of meaning in semiotics, namely denotation and connotation. The results of the analysis show the existence of explicit and implicit messages that reveal the dynamics of interaction between husband and sister-in-law, which reflect the complexity of interpersonal relationships and family dynamics. This finding is interpreted as a myth that represents cultural values, social norms, and communication challenges in the context of family relations.